Pellagra In An Alcoholic - Thappa Devinder Mohan; Karthikeyan Kaliaperumal (Wolters Kluwer Medknow Publications, 2002)
Pellagra is a nutritional disorder that occurs due to niacin deficiency. In the present day context, in western world, pellagra is confined to individuals who have improper food intake, such as psychiatry patients, alcoholics and recluses. Here with we report a case of pellagra occurring in a 60 year old male who was a chronic alcoholic.